Diplomacy in the European Union’s Energy Sector in the Context of Dependence on Russian Energy Imports .......... 163 - Borodulin, Wioleta (Oblicza dyplomacji, 2025)
This paper analyses the EU’s dependence on Russian energy and its shift after the 2022 invasion of Ukraine. Before the war, Russia supplied about 30% of the EU’s energy, but the conflict spurred a push for diversification, led by the initiatives like REPowerEU. Member states responded differently: Poland accelerated independence, while Hungary maintained ties with Russia. At the same time, Russia redirected energy exports to China, India, and Turkey to counter Western sanctions. Energy became a key diplomatic tool for both sides, shaping foreign policy and security strategies. Poland’s case illustrates successful diversification efforts.